Shang-Chi and the legend of the ten rings [videorecording (DVD)] - Cretton, Destin Daniel; Callaham, David, 1977-; Lanham, Andrew (Screenwriter); Liu, Simu, 1989-; Awkwafina, 1989-; Zhang, Meng'er, 1987-; Chen, Fala; Munteanu, Florian; Wong, Benedict; Yuan, Hua, 1950-; Yeoh, Michelle, 1963-; Kingsley, Ben, 1943-; et al. (Marvel Studios, 2021)
Shang-Chi must confront the past he thought he left behind when he's drawn into the web of the mysterious Ten Rings organization controlled by his father, a man who gained immortality and the desire for unlimited power when he acquired an ancient artifact centuries ago.